2017
DOI: 10.4236/tel.2017.76124
|View full text |Cite
|
Sign up to set email alerts
|

Keeping It Simple: Comparative Analysis of TFP across Manufacturing Industries and Major States of India

Abstract: The measurement of total factor productivity in Indian economic development has been greatly debated especially after economic reforms set in. While a fair amount of research is done on this subject, however the findings were lost in the shadow of complex econometric techniques. This paper is an honest attempt to simplify the complex area of productivity for a geographically multifaceted country-India. The paper carries out a comprehensive and comparative TFP (total factor productivity) analysis across 19 majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…According to the authors, patents filing, technology licensing and financial resources generated are not correlated rather, a nonconsistent pattern of patents filing and licensing existed amid all CSIR laboratories. Singh (2017) has reviewed the existing studies on measuring productivity found that the techniques suggested in those studies were complex for implementation. The author has also introduced a simple measurement technique for total factor productivity i.e.…”
Section: Public Sector Performance Managementmentioning
confidence: 99%
“…According to the authors, patents filing, technology licensing and financial resources generated are not correlated rather, a nonconsistent pattern of patents filing and licensing existed amid all CSIR laboratories. Singh (2017) has reviewed the existing studies on measuring productivity found that the techniques suggested in those studies were complex for implementation. The author has also introduced a simple measurement technique for total factor productivity i.e.…”
Section: Public Sector Performance Managementmentioning
confidence: 99%
“…Material input series has been deflated by a deflator which is computed as a weighted average of price indices for various input-output sectors. For each industry, WPI (wholesale price indices) have been used (Singh, 2017b). I used the input output table baselined for the year 1993-94 and published by CSO (Central Statistical Organization) for this purpose.…”
Section: Data and Variablesmentioning
confidence: 99%
“…It concludes that short term loans promote productivity. This is probably due to the fact that short term debt is used in working capital to en (Singh, 2017a(Singh, , 2017b. This, in turn, promotes productivity.…”
Section: Nexus Of Financial Obligations and Productivitymentioning
confidence: 99%
“…Therefore, 3PL provider would have more incentive and the high degree of values addition where input tax credit could be claimed. The entry in different states would become easy, and the delays in the transportation cost will be reduced [39].…”
Section: Literature Reviewmentioning
confidence: 99%